Consumption of ergogenic substances: An approach from participatory action research method (Impetus, 2021)
Among the various forms of body construction that are highlighted today, draws attention to the practices developed in gyms, and especially those that link university students. The increase in physical performance and the transformation of body image are usually the main objectives, and for this many students are making use of products designed for that purpose. Unfortunately, their consumption decision is based solely on the benefits they provide, without considering information about components, side effects and contraindications. However, pretending to be socially accepted and feeling admired are priority reasons for the potential repercussions of misuse. Therefore, understanding the knowledge, imaginaries, consumption practices and motivations for the use of ergogenic substances in university students who attend gym became the main objective of research in its first phase. The second phase was based on the results of the first one in order to structure and develop a methodology framed in the Participatory Action Research (PAR). The description and analysis of this second phase are the reason for writing this article. In this way, inputs will be established to address an intervention process (third phase) which is considered necessary to promote the generation of knowledge and critical decision making in students contemplating the possibility of using this type of substances.
Keywords: university students; imaginary; participatory action research; ergogenic products; body transformations